Does Reckless Driving Predict Road Traffic Accidents Among Commercial Drivers? - Ewere A. Aibangbe; Sunday A. Atunwa; Emmanuel E. Uye (Citakonsultindo, 2026)
Road traffic accidents have remained a major global concern due to their devastating social and economic effects on the individuals, families, society and the nation. While studies have addressed the non-human factors as the cause of road traffic accidents, studies addressing the human factors seem sketchy. Therefore, this study examines the predictive role of reckless driving on road traffic accidents among commercial drivers in Obio/Akpor in Rivers State, Nigeria. Cross-sectional survey design was adopted while purposive sampling technique was used to select the study population. Two validated questionnaires were used to collect data from 238 participants and analyzed using simple linear regression to test a hypothesis which was accepted at p<.001 level of significance. The result demonstrated that reckless driving significantly correlated with road traffic accidents among study participants, R2 =.570, F (1,236) = 270.614, p <.001. Furthermore, reckless driving significantly predicted road traffic accidents among commercial drivers (β = .755, p<.001). The study concludes that reckless driving significantly contributed to road traffic accidents among study participants. The study recommends all stakeholders should take proactive measures to checkmate reckless driving among commercial drivers to reduce road traffic accidents.